THE EFFECT OF WORK CULTURE AND WORK MOTIVATION ON THE PERFORMANCE OF CENTRAL BPS EMPLOYEES - Vera Citra Wulandari; Lisman Manurung; Soesilo Wibowo (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2022)
Simplification of the bureaucracy with minimal structure but rich in functions led to changes in the work culture of employees. Employees are required to be more proactive at work, not just waiting for instructions from the leadership to work. This study aims to determine the effect of work culture and work motivation on employee performance at Central BPS. This type of research is quantitative research. The population in this study were all civil servants of BPS on Jl. dr Soetomo Jakarta, totaling 1429 employees. Sampling was done by means of systematic sampling, as many as 303 employees. Data collection was carried out by survey method using google form. Data were analyzed by simple and multiple linear regression. Based on calculations using the Weight Least Square method for the variables of Work Culture (X1), Work Motivation (X2), and Employee Performance (Y), the regression equation can be made as follows Y= -1.1218 + 0.9203 X1 + 0.1180 X2. The results showed that work culture and work motivation simultaneously had a significant effect on the performance of Central BPS employees by 94.13 percent, while the remaining 5.87 percent was explained by other variables that were not included in the model used in the study. Partially, work culture and work motivation have a significant effect on the performance of Central BPS employees. The findings in this study are that sincere attitude is a work culture that has a strong influence on improving the performance of Central BPS employees and good interpersonal relationships can motivate Central BPS employees to improve their performance. To further strengthen the work culture, the organization's core values ​​should be stated in operational standards for the implementation of activities/tasks.